(untitled) (Tanzania Medical Journal, 2020)
Background The pathophysiology of sickle cell disease (SCD) is complex and involves nitric oxide depletion, increased inflammation/adhesion molecules and vaso-occlusion in addition to the chronic hemolytic anemia. This pathophysiology results in systemic clinical complications including recurrent episodes of severe pain, stroke, acute chest syndrome (ACS) and an increased susceptibility to infection. SCD severity varies among individuals and fetal hemoglobin (HbF) is known as a major modulator of the disease. To date, hydroxyurea (HU) is a known intervention that acts by increasing HbF in individuals with SCD. The increase in HbF reduces the risk of ‘sickling’ events and improves clinical outcomes. This is the first study on the use of HU in individuals with SCA in Tanzania. Methods A case-control study to determine the proportion, indications, clinical and laboratory outcomes of SCD patients with HU use was conducted at Muhimbili National Hospital in Dar Es Salaam, Tanzania. Results Forty-two patients with Sickle cell anemia (SCA) on HU treatment and 32 patients with SCA not on HU treatment were enrolled. The proportion of HU use by individuals with SCA at Muhimbili National Hospital was 10 per 1000. The mean HbF % was 9.8 ± 2.4 vs 6.2 ±1.4 for controls (P <0.001). Thirty (71.4%) were enrolled for HU treatment due to central nervous system (CNS) events, frequent painful crises 11(26.2%) and recurrent anemia 1(2.4%). Thirty-two SCA patients (76.2%) reported improvements after being on HU for at least six months. Of these, 91% reported no history of severe pain that required hospitalizations since they started HU. Twenty patients (66.7%) out of those with CNS events reported not to have experienced convulsions after HU initiation. Conclusions HbF was higher in patients who were on HU and had positive correlation with clinical outcomes. Further clinical trials are required to evaluate more effects of HU use among SCA individuals in Tanzania. Keywords: Sickle cell anemia, HU, Fetal hemoglobin, Tanzania.